Rapid evolution in native plants cultivated for ecological restoration: not a general pattern. (22nd September 2018) - Nagel, R.; Durka, W.; Bossdorf, O.; Bucharova, A.
Abstract: The growing number of restoration projects worldwide increases the demand for seed material of native species. To meet this demand, seeds are often produced through large‐scale cultivation on specialised farms, using wild‐collected seeds as the original sources. However, during cultivation, plants experience novel environmental conditions compared to those in natural populations, and there is a danger that the plants in cultivation are subject to unintended selection and lose their adaptation to natural habitats. Although the propagation methods are usually designed to maintain as much natural genetic diversity as possible, the effectiveness of these measures have never been tested. We obtained seed of five common grassland species from one of the largest native seed producers in Germany. For each species, the seeds were from multiple generations of seed production. We used AFLP markers and a common garden experiment to test for genetic and phenotypic changes during cultivation of these plants. The molecular markers detected significant evolutionary changes in three out of the five species and we found significant phenotypic changes in two species. The only species that showed substantial genetic and phenotypic changes was the short‐lived and predominantly selfing Medicago lupulina, while in the other, mostly perennial and outcrossing species, the observed changes were mostly minor. Agricultural propagation of native seed material for restoration can cause evolutionary changes, at least in some species. We recommend caution, particularly in selfing and short‐lived species, where evolution may be more rapid and effects may thus be more severe.